Analysis of Factors Related to Occurrence of Retaker UKMPPD Faculty of Medicine, University of Sriwijaya - Silvi Silvania (Community Medicine and Education Journal, 2020)
Medical education is a conscious and planned effort in formal education to produce graduates who have competencies in the fields of medicine or dentistry. Medical students who have gone through the undergraduate and professional stages of the doctor must take the competency exam (UKMPPD). The medical faculty of Sriwijaya University in the November 2016 period in the UKMPPD which was attended by 41 participants, found that only 9 people had successfully passed the competency exam. In Indonesia, the number of UKMPPD participants who have not graduated (retaker) at the end of 2017 is 2,494. This indicates that the number of UKMPPD retaker is still high in the Indonesian medical faculty. Student competency test results can be influenced by external factors and internal factors which include the value of try out, Grade Point Average (GPA), learning style, tutoring, length of study period, anxiety, family support and peer support. This research was conducted to identify factors related to the retaker of UKMPPD students at FK Unsri. The type of research used is quantitative analytical research with cross-sectional design with consecutive sampling technique. The population of this study were students who took the UKMPPD in January-October Unsri FK in 2018. The study sample was a portion of the students who took part in the UKMPPD FK Unsri Sriwijaya in 2018, amounting to 50 people. Data collected are primary data using questionnaires. Data analysis using univariate and bivariate analysis using the Chi-Square test. From this study obtained p-value <0.05 for the GPA variable, try out value, length of study period and anxiety. These results indicate that there is a significant relationship between GPA, try out value, length of study period and anxiety with the occurrence of UKMPPD retaker. While the learning and learning style variables obtained p-value> 0.05 which showed that there was no significant relationship between learning styles and learning guidance with the occurrence of the retaker student of UKMPPD of FK Unsri. There is a meaningful relationship between GPA, try out value, length of study period and anxiety with the occurrence of UKMPPD retaker student of FK Unsri and there is no significant relationship between learning styles and learning guidance with the occurrence of UKMPPD retaker student of FK Unsri.